Dictatorship survivors: testimonies of the Milton Santos Commission of Memory and Truth UFBA (Tempo e Argumento, 2022)
The article presents the oral collection built by the Milton Santos Truth Commission (UFBA) which made available on youtube thirty (30) reports of testimonies recordings with former UFBA students and professors about the coup and the dictatorship. The context of production of the narratives was marked by the 50th anniversary of the 1964 coup that updated the “war of memories” about the dictatorship, especially after the creation of the National Truth Commission in 2012. The text explores the testimonies privileging the impact of the coup of 1964 and the (post)AI-5 for the subjects.
Keywords: memory; Truth Comission; dictatorship